Synthesis of a 316L stainless steel-copper composite by laser melting - Kijoon Lee; V.Vinay K. Doddapaneni; Saereh Mirzababaei; Somayeh Pasebani; Chih-hung Chang; Brian K. Paul (Additive Manufacturing Letters, 2022)
This paper demonstrates a laser melting method to produce a metal matrix composite with a higher thermal conductivity compared to 316 L stainless steel using a Jettable Cu ink. A novel canister was used to control the oxygen level during laser processing to emulate a hybrid inkjet-powder bed fusion technique for doping the stainless steel powder bed with Cu precursor ink. The thermal conductivity of the composite was found to be 187% higher than that of 316 L stainless steel, while the microhardness decreased by 39%. Microstructural results show opportunities to further enhance the thermal conductivity and mechanical properties of the composite by eliminating interfacial cracking.